2017
DOI: 10.5376/ijh.2017.07.0024
|View full text |Cite
|
Sign up to set email alerts
|

Development of Vegetable Nutrition Garden Model For Diet Diversification and Improved Nutrition Security of Urban and Peri-urban Households

Abstract: Vegetables help combat malnutrition and diversify diets. Dietary diversification balances the diet by enhancing supply of essential micro-nutrients leading to improved health, enhanced thinking ability and increased efficiency. Improved vegetable nutrition garden is better than traditional homestead vegetable garden. The improved model involves many crops that can be repeatedly harvested to meet a family's vegetable needs throughout the year. The crops and their varieties are scientifically selected to be high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Small mixed vegetable gardens can provide a significant portion of the recommended daily requirement for protein (10%-20%), iron (20%), calcium (20%), vitamin A (80%) and vitamin C (100%) [16]. Similar results were found in this study also.…”
Section: Discussionsupporting
confidence: 89%
“…Small mixed vegetable gardens can provide a significant portion of the recommended daily requirement for protein (10%-20%), iron (20%), calcium (20%), vitamin A (80%) and vitamin C (100%) [16]. Similar results were found in this study also.…”
Section: Discussionsupporting
confidence: 89%
“…There are many studies that linked the effectiveness of kitchen garden in enhancing dietary diversity [ 60 ]. For instance, kitchen gardens were observed to significantly influence dietary diversity among landless households in Myanmar and enhances food security of households [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in different countries have demonstrated that kitchen gardens improve food security of households [ [27] , [28] , [29] , [30] ]. Moreover, it is evident from the literature that homestead food production interventions increase the production of micronutrient-rich foods, such as crops and fruits [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 99%